2017
DOI: 10.1016/j.jbusvent.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Diversification, risk, and returns in venture capital

Abstract: We explore an alternative, finance theory-based explanation for the documented positive relationship between fund diversification (or lack of fund specialization) and performance in venture capital (VC). Our proposed "Risk Hypothesis" posits that the expected negative impact of diversification on fund risk induces fund managers to endogenously select riskier investments, which in turn leads to higher performance of more diversified funds. While other channels may also be at play, we provide results that suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…This unique feature of the data enabled us to construct the herding measures developed previously, which was essential to explore the determinants of herding behaviour of the PE funds and estimating the relationship between the fund-level herding and performance. Other studies have also used the CEPRES database (e.g., Buchner, Mohamed, and Schwienbacher, 2017;Cumming, Schmidt, and Walz, 2010;Franzoni, Nowak, and Phalippou, 2012;Krohmer, Lauterbach, and Calanog, 2009).…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations
“…This unique feature of the data enabled us to construct the herding measures developed previously, which was essential to explore the determinants of herding behaviour of the PE funds and estimating the relationship between the fund-level herding and performance. Other studies have also used the CEPRES database (e.g., Buchner, Mohamed, and Schwienbacher, 2017;Cumming, Schmidt, and Walz, 2010;Franzoni, Nowak, and Phalippou, 2012;Krohmer, Lauterbach, and Calanog, 2009).…”
Section: Datamentioning
confidence: 99%
“…A lack of anonymity can encourage PE firms to only provide information on better performance and suppress poor performance. Buchner, Mohamed, and Schwienbacher (2017) provide detailed discussions of the CEPRES data collection process, the information available on PE firms, and how the database compares with other databases on PE funds.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Petty and Martin (1983) and Buchner et al (2017) revealed that VC is a high-risk and high-return investment. Therefore, investments should be diversified into different portfolios to ensure that investment risks can be minimised.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, venture capital companies remain cautious in determining investment. In accordance to Buchner, Abdulkadir and Armin (2017), the investment decisions made by the managers in the venture capital companies are reflected in serious investment analysis, especially to assess the expertise in fund management by the start-up companies as potential investees. Lee (2017) in his research on the peer-network identification and measurement of the venture capital role towards start-up companies found that many start-up companies have partnered with venture capital companies based on the provided capital assistance and the success of creating innovative products made by the start-ups.…”
Section: Introductionmentioning
confidence: 99%